A difference-in-difference analysis comparing a control and an intervention social housing area. (30th September 2020) - Nygaard, S; Srivarathan, A; Mathisen, J; Lund, R
Abstract: Often an intervention is applied in an area (e.g. community, municipality) without it being an experiment and without a control group, this can be categorized as a natural experiment. Such a situation offers the opportunity to exploit exposure contrasts between areas regarding the specific intervention for evaluation. In the present study, we will employ the difference-in-difference approach to evaluate the natural experiment (the structural intervention) comparing measures of health and social factors retrieved from registers in the two social housing areas before and after the intervention. A 'natural experiment' study comparing individual and aggregated level differences in register-based information on health and social variables across time including the entire study period is included in the research project. The population includes all residents with an address in the study area and the control area at any point during the years 2015-2025 (∼3, 000 residents in each area). All residents are linked to the Danish social and health registers by the unique personal identification number, which makes it possible to follow all permanent and former residents over time. Hereby we plan to study if the structural changes (the structural intervention, the 'natural experiment') give rise to differences in health (such as use of general practitioner, hospitalizations, use of selected medications) and social factors (e.g. divorces, income levels, unemployment) compared to the control area. The control area is representing a similar social housing area in the same municipality, which will not undergo structural changes until 2023. Findings will be evaluated drawing upon knowledge gained from the entire study from surveys and qualitative interviews as well experiences from the interventions. In this presentation, we wish to discuss how best to include the knowledge based on other methodologies in the register-based analyses.